An unexpected recovery of patients with pulmonary arterial hypertension and SARS‐CoV‐2 pneumonia: a case series. (1st September 2020) - Scuri, Piermario; Iacovoni, Attilio; Abete, Raffaele; Cereda, Alberto; Grosu, Aurelia; Senni, Michele
Abstract : Since the beginning of the SARS‐CoV‐2 outbreak, few cases of COVID‐19 pneumonia in patients with pulmonary arterial hypertension have been reported. We present four patients with known history of PAH admitted to our hospital with SARS‐CoV‐2 pneumonia to analyze the impact of this disease on their clinical outcome.